Effect of recovery tapping on yield potential of rubber(Hevea brasiliensis) trees - Silva T U K; Nugawela A; Rodrigo V H L; Serasinghe P (Journal of the Rubber Research Institute of Sri Lanka, 2001)
Wet tapping panels are not tapped as it leads to panel diseases, law yields (drying of panels) and wastage of latex. Therefore depending on the area of the cultivation ca. 15-34;of the crop is lost each year. Amongst the different agrotechnologies recommended to overcome this crop loss, recovery tapping is frequently done in both pplantations and smallholdings. In this study the effect of 0(RT-0), 3(RT-3), 4(RT-4), amd 5(RT-5) recovery tappings/tree/month on yield and some yield related parameters of two widely grown clones was tested. Total dry rubber yield per tree per month was highest in RT-5 and lowest in RT-0 during first two months of the study. On the third month the RT-0 gave the highest yield/tree/month in clone RRIC 100 whilst in RRIC 121, RT-5 recorded a marginally high yield. During the initial two months of the study all treatments with recovery tapping recorded a higher g/t/t than from the no recovery tapping treatment in both clones. However, in the third month of the study treatments with recovery tapping recorded a significantly lower g/t/t in clone RRIC 100. In RRIC 121 though the g/t/t was low, the difference was not significant. Excessive recovery tapping continuously for periods more than 2 months resulted in significantly lower latex volumes and DRC. These can be attributed to the lower g/t/t and monthly total yields with excessive recovery tapping. The yield per unit bark consumed also declines when excessive recovery tapping is undertaken. It can therefore be concluded that recovery tapping when done excessively will not result in higher yields than what can be achieved with the recommended number of recovery tappings. Also there is evidence that some clones, e.g. RRIC 121 may withstand relatively more number of recovery tappings a month than others.
Keywords: Latex volume; Recovery tapping; Rubber; Tapping intensity; Yield